2017
DOI: 10.1177/155698451701200613
|View full text |Cite
|
Sign up to set email alerts
|

Totally Endoscopic Cardiac Surgery for Atrial Septal Defect Repair on Beating Heart without Robotic Assistance in 25 Patients

Abstract: The aim of the study was to investigate the effectivity and safety of totally endoscopic cardiac surgery without robotic assistance for atrial septal defect (ASD) closure on beating hearts. Methods: Twenty-five patients (adults/children: 15/10) underwent ASD closure using nonrobotically assisted totally endoscopic approach on beating heart. Three 5-mm trocars and one 12-mm trocar were used, only the superior vena cava is snared, filling the pleural and pericardial cavities with CO 2 , and the heart was beating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In ASD repair, a beating heart with pleural and pericardial cavities filled with CO 2 has many advantages, including (1) safety, (2) time savings and limited bleeding due to no touch on the ascending aorta, and (3) a more extensive surgical field. 1517 Through this study, we found that the absence of a transthoracic clamp allowed the SVC and related structures to be observed more clearly. In addition, the surgical steps on the SVC, including the SVC snaring, the first patch, and the second patch, could be done quickly with average times of 8.8 ± 3.4 min, 25.0 ± 9.6 min, and 25.9 ± 9.0 min, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 64%
“…In ASD repair, a beating heart with pleural and pericardial cavities filled with CO 2 has many advantages, including (1) safety, (2) time savings and limited bleeding due to no touch on the ascending aorta, and (3) a more extensive surgical field. 1517 Through this study, we found that the absence of a transthoracic clamp allowed the SVC and related structures to be observed more clearly. In addition, the surgical steps on the SVC, including the SVC snaring, the first patch, and the second patch, could be done quickly with average times of 8.8 ± 3.4 min, 25.0 ± 9.6 min, and 25.9 ± 9.0 min, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 64%
“…Because the pressures of the arterial line were significantly raised immediately after starting CPB, an additional arterial cannula was directly placed into left common FA to reduce the pressure. 4 We chose arterial cannula, which is 4F smaller in size compared with a standard size based on patient's weight (10F and 12F vs. 14F and 16F, respectively). With the aim of reducing the arterial pressure, this method not only helped save the time (compared with sewing another graft) but also secured leg perfusion.…”
Section: Discussionmentioning
confidence: 99%